The uptake and distribution of selected heavy metals in the freshwater crab, Potamonautes perlatus (Milne Edwards), in the Eerste River, Western Cape - Snyman, Reinette Georgenie (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScAgric (Zoology))--University of Stellenbosch, 1996.